Design and Development of Reverse Slot Blot for the Simultaneous Detection of Rare and Regional Specific Mutations in the Beta Globin Gene in Khuzestan Province of Iran - Galehdari, Hamid (Indian J Hematol Blood Transfus, 2021)
Beta-thalassemia is the most frequent hemoglobin disorder in Iran resulting from disrupting mutations in the beta globin (HBB) gene that causes decreased or complete absent of beta-globin chains. The screening of beta-thalassemia minor and major individuals and prenatal diagnosis is important for familial planning. Therefore, it is essential, depending on the ethnicity and local frequency of changes, to develop a rapid and accurate method for molecular diagnosis of beta-thalassemia. Here, we developed reverse slot blot (RSB) assay for the simultaneous detection of six common pathogenic changes in the HBB gene (-88, -28, IVSII-745, IVSII-848, Codon 6 [G → A] for HbC, Codon 6 [A → T] for HbS) in the Khuzestan Province of Iran. We designed normal and mutant oligonucleotide probes for each selected mutation and fixed them on positively charged nylon membrane. In the next step, a multiplex-polymerase chain reaction (PCR) performed for the amplification of the entire HBB gene using labelled 5′-biotinylated primers. The PCR products were hybridized to immobilized oligonucleotide probes on the membrane at the appropriate temperature. Finally, we developed the membrane by chemically colorimetric reaction using nitro-blue tetrazolium-5-Bromo-4-chloro-3-indolyl phosphate. For the best probe concentration, we made a serial dilution of probe pairs for each mutation. The optimal probe concentration for each mutation varied from 25 to 50 pmol. In the next step, DNA samples from homozygous affecting individuals were subjected for multiple PCR. Hybridization of each PCR products on the nylon membrane with probe pairs revealed specific bands with expected signal intensity without any background. Our designed RSB test is a rapid, sensitive and cost-effective method for screening of regional specific beta-thalassemia mutations in the Khuzestan population of Iran, which might be extended for the detection of any desired pathogenic changes.